Tipologinės pastabos dėl giminės kategorijos formavimosi - Palmaitis, Letas (Baltistica, 1978)
Typological notes on the development of gender In the article the linguistic universal is observed, according to which the appearing of the category of gender is connected with the development of the morphological opposition of nominative : accusative. In those systems, where the special form of accusative is attested, the category of gender does exist. It is stated, that the appearing of gender is the morphological phenomenon connected with the changes in the very structure of the language, and an attempt is made to show the development of this category out of the previous category of the grammatical classes. The principal difference between them is that the category of gender is defined purely morphologically, its relation to semantics being mere a non-categoreal relic, while the category of classes has the indispensable semantical definition. As an illustration to the development of gender, the appearing of the Afro-Asiatic marker of feminine -a (+t as a glide by joining the case inflections) is explained to be the fossilized ending of the absolutive case. This -a is a morphologized variant of the consonantal morpheme ending, resp. of that of the bare stem form of absolutive, where the alternation of -Ca ‖ -C is attested. The analogous morphologization of the components -Ca, -C → -a ‖ -ø must have produced the thematic (-a, traditionally- *-o) and the athematic (-ø) markers of the corresponding types of the Indo-European declension. The latter idea is illustrated by the analogous possibility in the Kartvelian pairs of the dat./loc. adgilas < *adgila +s : adgilsa < *adgil + sa type.